Market dynamics when participants rely on relative valuation - Sean Lavelle (Kiel Institute for the World Economy (IfW), 2016)
Relative-valuation is a technique whereby financial analysts estimate the value of an asset by comparing it to its peers. The author formalizes the decision-making structure of a relativevaluation strategy and simulate a market defined by its use. He finds that when the distribution of peer valuation-multiples is skewed high or low, the market will tend to equilibrate over or undervalued, respectively. He furthers this analysis by looking at the effect that subjective analyst adjustments of market multiples might have and concludes that they have the potential to be highly destabilizing.
Keywords: G02; D53; 330; Relative valuation; inefficient; EMH; simulation; comparative valuation